수중로봇용 덕트 추진기의 설계 및 성능해석 - 김경진(Kyung-Jin Kim); 이두형(Doo-Hyoung Lee); 박원규(Warn-Gyu Park); 박한일(Han-Il Park) (Han-guk haeyang gonghak hoeji (Online), 2012)
Underwater robots are generally used for the construction of seabed structures, deep-sea ecosystem research, ocean energy development, etc. A ducted marine propulsor is widely used for the thruster of an underwater robot because of its collision protection, efficiency increase, cavitation reduction, etc. However, the flow of a ducted propeller is very complex because it involves strong flow interactions between the blade impeller and duct. The present work aimed to design a ducted propeller using 2-D strip theory and CFD analysis. The hydrodynamic forces (i.e. and ) were computed to set the local angle of attack in a spanwise direction of the propeller blade. After the propeller design, performance coefficients such as the thrust, torque, and efficiency were computed to check whether the designed performance was achieved. To validate the present analysis, the thrust was compared with experimental data and good agreement was obtained.